Curcuminoids Limit Neutrophil‐Mediated Reperfusion Injury in Experimental Stroke by Targeting the Endothelium. (9th August 2013) - Funk, Janet L.; Frye, Jennifer B.; Davis‐Gorman, Grace; Spera, Allison L.; Bernas, Michael J.; Witte, Marlys H.; Weinand, Martin E.; Timmermann, Barbaba N.; McDonagh, Paul F.; Ritter, Leslie
Abstract Objective We sought to test the hypothesis that turmeric‐derived curcuminoids limit reperfusion brain injury in an experimental model of stroke via blockade of early microvascular inflammation during reperfusion. Methods Male Sprague Dawley rats subjected to MCAO/R were treated with turmeric‐derived curcuminoids (vs. vehicle) 1 hour prior to reperfusion (300 mg/kg ip). Neutrophil adhesion to the cerebral microcirculation and measures of neutrophil and endothelial activation were assayed during early reperfusion (0–4 hours); cerebral infarct size, edema, and neurological function were assessed at 24 hours. Curcuminoid effects on TNFα‐stimulated human brain microvascular endothelial cell (HBMVEC) were assessed. Results Early during reperfusion following MCAO, curcuminoid treatment decreased neutrophil rolling and adhesion to the cerebrovascular endothelium by 76% and 67% and prevented >50% of the fall in shear rate. The increased number and activation state (CD11b and ROS) of neutrophils were unchanged by curcuminoid treatment, while increased cerebral expression of TNFα and ICAM‐1, a marker of endothelial activation, were blocked by >30%. Curcuminoids inhibited NF‐κB activation and subsequent ICAM‐1 gene expression in HBMVEC. Conclusion Turmeric‐derived curcuminoids limit reperfusion injury in stroke by preventing neutrophil adhesion to the cerebrovascular microcirculation and improving shear rate by targeting the endothelium.